High-density platinum-loaded platinum-carbon catalyst as well as preparation method and application thereof
Co-doped carbon nanotube surfaces by co-doping cobalt-nitrogen-carbon bonding is formed, which promotes high-density nucleation growth of platinum nanoparticles, solves the problems of low loading and uneven distribution of platinum carbon composite catalysts, and significantly improves the Catalytic activity and stability achieve efficient oxygen reduction reaction performance.
Patent Information
- Application Number
- CN202411355993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing platinum carbon composite catalysts have low loading of platinum nanoparticles and uneven distribution in proton exchange membrane fuel cells, resulting in low catalytic activity and unstable in the electrochemical process, which can easily lead to the fall of platinum nanoparticles and decrease in catalytic activity.
By co-doping the surface of carbon nanotubes, cobalt-nitrogen-carbon bonding is formed, and the cobalt atom cluster serves as nucleation sites to promote the uniform distribution of platinum nanoparticles and high-density nucleation growth, forming a high-density platinum load Platinum carbon catalyst.
The high-density loading and narrow particle size distribution of platinum nanoparticles are achieved, which significantly improves catalytic activity and stability and enhances electrochemical performance.
Smart Images

Figure CN119252949A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a high-density platinum-loaded platinum-carbon catalyst and a preparation method and application thereof. Background Art
[0002] Due to the strong tolerance of platinum to acid, platinum (Pt)-based catalyst materials remain the most practical catalysts for the cathode oxygen reduction (ORR) catalytic reaction of proton exchange membrane fuel cells. However, the high cost and scarcity of Pt hinder its large-scale application in proton exchange membrane fuel cells. Therefore, in order to reduce the required amount of Pt, the technical development direction of early platinum-based catalysts was to maximize its atomic utilization by synthesizing ultrafine nanoparticles. However, the large surface energy of platinum nanoparticles causes them to easily agglomerate to form larger particles during the electrochemical process, resulting in a decrease in their long-term catalytic activity. In order to solve these problems, it is necessary to use materials with high surface areas as anchoring sites to reduce their agglomeration and improve their catalytic performance. In addition to improving the dispersion effect of platinum nanoparticles, support materials can also improve the ORR catalytic activity of the platinum component and improve its stability.
[0003] Carbon nanotubes (CNTs) have been proven to be a good carrier material due to their excellent properties (such as structural stability, high crystallinity, good conductivity, high surface area and good mechanical properties). For proton exchange membrane fuel cells that work for a long time under acidic conditions, their graphitized structure gives them highly stable electrochemical properties. However, as for the carbon nanotubes themselves, their surface graphitized structure makes them chemically inert. During the material composite process, there are few anchoring sites adsorbed on their surface, and the interaction formed with the metal material is too weak to stabilize the metal particles on the surface during the electrochemical process. Therefore, in order to increase the number of anchoring sites, researchers usually use various chemical methods to functionalize them and improve their metal nanoparticle adhesion ability. The most commonly used method is to introduce oxygen-containing groups.
[0004] For example:
[0005] Chinese patent CN115084547A disperses multi-walled carbon nanotubes in a nitric acid solution, refluxes at a certain temperature for a certain time, breaks the CC bonds on the surface of the multi-walled carbon nanotubes and forms dangling bonds or oxygen-containing group bonds, and deposits metal salts on the surface of the acidified multi-walled carbon nanotubes through adsorption, and then calcines in a mixed atmosphere of hydrogen and nitrogen to form a carbon-supported platinum alloy catalyst.
[0006] Chinese patent CN113113624A mixes a multi-walled carbon nanotube carrier with potassium permanganate and then calcines it to cover the surface with an in-situ grown manganese oxide hydrophilic functional layer, then uniformly disperses platinum nanoparticles on the manganese oxide hydrophilic layer, and uses manganese tetraoxide to replace the nano-platinum particles and deposit them on the surface of the carbon nanotube coating.
[0007] Chinese patent CN113871645A can prepare platinum nanoparticles of similar size and uniform shape through precursor platinum salt. Then, the carbon nanotubes are oxidized with potassium permanganate to prepare a carrier containing surface oxidized groups. Platinum nanoparticles are loaded on carbon nanotubes to obtain a catalyst with uniform morphology and good oxygen reduction reaction performance.
[0008] Chinese patent CN101298048A first purifies carbon nanotubes with concentrated nitric acid, and then treats with a mixed acid of hydrogen peroxide and concentrated sulfuric acid to obtain functionalized carbon nanotubes. Then, the functionalized carbon nanotubes, part of the platinum salt and all the transition metal M salts are stirred and refluxed in a polyol solvent for a certain period of time, and the remaining platinum salt is added to continue to reflux, so as to prepare a platinum alloy catalyst material on the surface of the carbon nanotubes.
[0009] Chinese patent CN102476062B discloses a platinum catalyst supported by carbon nanotubes and a preparation method thereof, wherein carbon nanotubes are mixed with chitosan solution to prepare a composite material, which is then used to support platinum. The preparation process omits the pre-treatment processes such as acidification and oxidation of carbon nanotubes, but the active sites are still lacking, resulting in aggregation of platinum particles.
[0010] Carbon nanotubes are a highly graphitized material. Their graphitized structure gives proton exchange membrane fuel cells that work for a long time under acidic conditions highly stable electrochemical properties. However, the surface of carbon nanotubes is too inert, which is not conducive to the deposition of platinum nanoparticles. The deposited platinum nanoparticles are sparse, the particle size is too large, and the catalytic activity is low.
[0011] These composite catalysts improve the surface anchoring sites by functionalizing the surface of carbon nanotubes so that the metal material can be better bonded to the surface of the carbon material. However, whether it is surface oxidation or the use of oxides and chitosan and other materials to functionalize carbon nanotubes, it is impossible to form uniform defect sites on the surface of carbon nanotubes, resulting in uneven distribution of anchoring sites, which causes platinum particles to aggregate to a certain extent during the nucleation process, and it is impossible to form finer and uniform platinum nanoparticles. In addition, oxygen-containing functional groups are extremely unstable and easily fall off during long-term electrochemical discharge, thereby weakening the adhesion between platinum nanoparticles and carbon nanotubes, causing platinum nanoparticles to fall off and further loss of catalytic activity. Therefore, the design and preparation of platinum-carbon composite catalysts with both high activity and stability is still an important technical difficulty in related fields. Summary of the invention
[0012] The purpose of the present invention is to give full play to the advantages of the highly graphitized structure of carbon nanotubes in electrochemical stability, and to propose a high-density platinum-loaded platinum-carbon catalyst and a preparation method thereof, in view of the problem that the ORR catalytic activity of the platinum-carbon composite catalyst is not high due to the low loading amount of platinum nanoparticles on the surface of the carbon nanotube carrier, uneven distribution and wide particle size distribution.
[0013] The invention discloses a high-density platinum-loaded platinum-carbon catalyst, comprising cobalt-nitrogen co-doped carbon nanotubes, the surface of which is modified with cobalt atoms and nitrogen atoms to form cobalt-nitrogen-carbon bonds, and the cobalt atoms use nitrogen atoms as nucleation sites to form a large number of uniformly distributed cobalt atom clusters on the carbon nanotubes; and platinum nanoparticles use the uniformly distributed cobalt atom clusters as nucleation sites to grow on the surface of the carbon nanotubes.
[0014] Furthermore, the particle size of the platinum nanoparticles ranges from 1.5 to 4.5 nm, and the average particle size is 2.9±2 nm.
[0015] Furthermore, the diameter of the carbon nanotubes is selected from 1 to 100 nm.
[0016] A method for preparing a high-density platinum-supported platinum-carbon catalyst of the present invention comprises the following steps:
[0017] S1, dispersing oxidized carbon nanotubes in deionized water, adding a cobalt-containing precursor and a nitrogen source to obtain a mixed dispersion;
[0018] S2, freeze-drying the mixed dispersion in step S1 and then calcining it to obtain a cobalt-nitrogen co-doped carbon nanotube material;
[0019] S3, the cobalt-nitrogen co-doped carbon nanotube material prepared in step S2 is dispersed in a solvent, a platinum salt solution is added, the mixture is heated to reflux, filtered and dried, and a high-density platinum-loaded platinum-carbon catalyst is prepared.
[0020] Furthermore, the preparation method of the oxidized carbon nanotubes is to use a strong oxidant and a strong acid to modify the surface of the carbon nanotubes, and then wash them to obtain the oxidized carbon nanotubes.
[0021] Furthermore, the diameter of the carbon nanotube material is selected from 1 to 100 nm; the strong oxidant includes one or more of potassium dichromate, potassium permanganate, and hydrogen peroxide; and the strong acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.
[0022] Furthermore, in step S1, the cobalt-containing precursor is selected from one or more of cobalt metal acetate, cobalt metal nitrate, and cobalt metal chloride.
[0023] Furthermore, in step S1, the nitrogen source is selected from one or more of dimethylimidazole, urea, and dicyandiamide nitrogen-containing polymers.
[0024] Furthermore, in step S3, the calcination temperature is 600-1000° C. and the calcination time is 1-4 hours.
[0025] Furthermore, in step S3, the solvent is selected from oleylamine, ethylene glycol, or a mixed solution of ethylene glycol and water.
[0026] Furthermore, in step S3, the reflux temperature is selected from 100-180° C.; and the reflux time is selected from 1-5 h.
[0027] A high-density platinum-loaded platinum-carbon catalyst prepared by the above-mentioned preparation method.
[0028] An application of the high-density platinum-loaded platinum-carbon catalyst as described above in a hydrogen fuel cell.
[0029] The present invention performs surface doping on oxidized carbon nanotubes by using cobalt and nitrogen. The nitrogen atoms on the oxidized carbon nanotubes first serve as nucleation sites for cobalt atom clusters to form cobalt-nitrogen-carbon bonds. The strong interaction between the cobalt atom clusters and the platinum metal further promotes the selective adsorption and deposition of platinum on the surface. The large number of cobalt atom clusters evenly distributed on the surface of the oxidized carbon nanotubes enriches the nucleation sites for platinum nanoparticles and forms a high-density surface attachment layer. The strong interaction between platinum and cobalt is utilized to achieve high-density nucleation growth of platinum on the surface of the oxidized carbon nanotubes, thereby obtaining platinum nanoparticles with small particle size and very narrow particle size distribution.
[0030] Compared with unmodified carbon nanotube-loaded platinum nanoparticles, the high-density platinum-loaded platinum-carbon catalyst prepared by the present invention has platinum nanoparticles with high-density loading, narrow particle size distribution, and small particle size. In addition, the electron compensation effect of the formed cobalt-nitrogen chemical bonds on the platinum nanoparticles further modulates the electronic state density of the platinum nanoparticles, and the catalytic activity of the composite catalyst is significantly enhanced, and the stability is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a scanning electron microscope image of the catalyst prepared in Comparative Example 1;
[0032] Figure 2 This is a scanning electron microscope image of the catalyst prepared in Example 3;
[0033] Figure 3 This is a transmission electron microscope image of the catalyst prepared in Example 3;
[0034] Figure 4 This is a transmission particle size distribution diagram of the catalyst prepared in Example 3;
[0035] Figure 5 It is a comparison chart of cyclic voltammetry test results of Example 3, Comparative Example 1, and Premetek 20% Pt / C commercial platinum-carbon catalyst;
[0036] Figure 6 This is a comparison chart of polarization curve test results of Example 3, Comparative Example 1, and Premetek 20% Pt / C commercial platinum-carbon catalyst. DETAILED DESCRIPTION
[0037] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0038] Embodiment 1:
[0039] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0040] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 100 mg of cobalt acetate were dissolved in 100 ml of water, stirred evenly with ultrasonic waves, and then freeze-dried. The dried sample was then heated at 5 °C / min and calcined at 800 °C for 2 h to obtain a cobalt-nitrogen modified carbon nanotube material.
[0041] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, and after ultrasonication for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0042] Embodiment 2:
[0043] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0044] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 200 mg of cobalt acetate were dissolved in 100 ml of water, ultrasonically stirred and freeze-dried, and then the dried sample was heated at 5 °C / min and calcined at 800 °C for 2 h to obtain cobalt-nitrogen modified carbon nanotube material.
[0045] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0046] Embodiment three:
[0047] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0048] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 250 mg of cobalt acetate were dissolved in 100 ml of water, ultrasonically stirred and freeze-dried, and then the dried sample was heated at 5 °C / min and calcined at 800 °C for 2 h to obtain cobalt-nitrogen modified carbon nanotube material.
[0049] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0050] Embodiment 4:
[0051] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0052] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 400 mg of cobalt acetate were dissolved in 100 ml of water, stirred evenly with ultrasonic waves, and then freeze-dried. The dried sample was then heated at 5 °C / min and calcined at 800 °C for 2 h to obtain a cobalt-nitrogen modified carbon nanotube material.
[0053] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0054] Embodiment five:
[0055] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0056] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 250 mg of cobalt nitrate were dissolved in 100 ml of water, ultrasonically stirred and freeze-dried, and then the dried sample was heated at 5 °C / min and calcined at 800 °C for 2 h to obtain cobalt-nitrogen modified carbon nanotube material.
[0057] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0058] Embodiment six:
[0059] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0060] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 250 mg of cobalt acetate were dissolved in 100 ml of water, stirred evenly by ultrasonication, and then freeze-dried. The dried sample was then heated at 5 °C / min and calcined at 900 °C for 2 h to obtain a cobalt-nitrogen modified carbon nanotube material.
[0061] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0062] Embodiment seven:
[0063] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0064] (2) 100 mg of modified carbon nanotubes, 2.5 g of urea, and 250 mg of cobalt acetate were dissolved in 100 ml of water, stirred evenly by ultrasonication, and then freeze-dried. The dried sample was then heated at 5 °C / min and calcined at 700 °C for 2 h to obtain a cobalt-nitrogen modified carbon nanotube material.
[0065] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a high-density platinum-supported platinum-carbon catalyst.
[0066] Comparative Example 1:
[0067] (1) Add 1.2 g of carbon nanotubes to 100 ml of concentrated sulfuric acid, stir for 1 h, then slowly add 6 g of potassium permanganate, react for 4 hours, dilute with water, add appropriate amounts of hydrogen peroxide and hydrochloric acid, stir overnight, centrifuge and filter, and freeze-dry to obtain modified carbon nanotubes.
[0068] (2) 100 mg of modified carbon nanotubes were added to a crucible, the temperature was increased at 5°C / min, and calcined at 800°C for 2 h, and the annealed powder sample was taken out.
[0069] (3) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a platinum-carbon catalyst with carbon nanotubes as the carrier.
[0070] Comparative Example 2:
[0071] (1) 100 mg of raw carbon nanotubes were added to a crucible, the temperature was increased at 5 °C / min, and calcined at 800 °C for 2 h. The annealed powder sample was taken out.
[0072] (2) Add 30 mg of the sample prepared in step (2) above to 30 ml of a mixed solution of ethylene glycol and water, perform ultrasonic treatment for 30 min, add 2 ml of a 10 mg / ml hexachloroplatinic acid solution, stir evenly, heat under reflux at 120° C. for 2 h, and then centrifuge and dry the cooled sample to prepare a platinum-carbon catalyst with carbon nanotubes as the carrier.
[0073] according to Figure 1 and Figure 2 The scanning electron microscope (SEM) images shown in the figure show the particle size and dispersion of platinum nanoparticles attached to the surface of carbon nanotubes before and after modification. Figure 1 As shown, comparative example 1 shows that the platinum particles on the surface of functionalized carbon nanotubes are distributed in a disordered manner. The figure shows that although smaller platinum nanoparticles are formed in a part of the area, some particles still aggregate during the growth process, and some platinum particles are adsorbed together in a large range. This is due to the insufficient and uneven distribution of anchor points on the surface, which leads to the agglomeration of some platinum nanoparticles. Figure 2This is a scanning electron microscope image of the catalyst prepared in Example 3. Figure 2 As shown, Example 3 is a carbon nanotube modified with cobalt and nitrogen, and its surface shows smaller platinum nanoparticles, and platinum particles (NPs) are evenly and densely dispersed on the carbon nanotube carrier. It can be found that the incorporation of cobalt plays an important role in Pt dispersion and particle size control, achieving a significant reduction in particle size.
[0074] like Figure 3 We used high-resolution transmission electron microscopy (HR-TEM) to characterize Example 3. Figure 4 This is the transmission particle size distribution diagram of the catalyst prepared in Example 3; the particle size range of the platinum nanoparticles is 1.5-4.5nm, and the average particle size is 2.9±2nm, which further verifies the particle size and distribution of the platinum particles on the surface of the cobalt and nitrogen modified carbon nanotubes.
[0075] like Figure 5 The cyclic voltammetry test results of Example 3, Comparative Example 1, and Premetek 20% commercial platinum-carbon catalyst are shown in the figure. By comparing the hydrogen adsorption and desorption peaks, it can be found that the electrochemical active area of the catalyst prepared by functionalized carbon nanotube material loaded with platinum nanoparticles (Example 3) is significantly improved compared with the catalyst prepared by functionalized carbon nanotube loaded with platinum nanoparticles (Comparative Example 1). This is because the carbon nanotubes are surface-modified by cobalt and nitrogen heteroatoms. The heteroatoms on the carbon nanotubes can serve as nucleation sites, which can promote the deposition of well-dispersed platinum nanoparticles and effectively improve the utilization rate of active sites on the surface of platinum nanoparticles.
[0076] Figure 6 This is a comparison diagram of polarization curves of Example 3, Comparative Example 1, and Premetek 20% commercial platinum-carbon catalyst. In the figure, the half-wave potential corresponding to Example 3 is much larger than the half-wave potential of Comparative Example 1 and the commercial platinum-carbon catalyst, indicating that the Co-N structure formed by the incorporation of cobalt and nitrogen into the carbon nanotube structure has a certain regulatory effect on the electronic structure of the platinum nanoparticles, thereby enhancing the oxygen reduction activity of the catalyst.
[0077] The performance indicators of the catalysts prepared in various embodiments and comparative examples and commercial platinum-carbon catalysts tested are shown in the following table:
[0078]
[0079] As can be seen from the above table, in Examples 1-4, as the content of cobalt relative to the carbon nanotube material increases, the half-wave potential of the catalyst first increases and then decreases. This is because as the cobalt atoms increase, the cobalt-nitrogen chemical bonds formed increase accordingly. When the cobalt content reaches a certain level, the combination between cobalt and nitrogen reaches saturation, and cobalt nucleates alone on the carbon surface to occupy some defects, which has a negative effect on the nucleation of platinum on its surface. In Examples 6, 3, and 7, the calcination temperature of step (2) changes from high to low, and the half-wave potential of the catalyst first increases and then decreases. This is because as the calcination temperature increases, the cobalt-nitrogen-carbon bonding gradually increases. Too high a temperature will lead to enhanced graphitization of the carbon nanotube surface, which is not conducive to the formation of bonds between cobalt-nitrogen-carbon, further reducing the activity of the catalyst.
[0080] For matters not mentioned above, the prior art applies.
[0081] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-density platinum-supported platinum-carbon catalyst, characterized in that: It includes cobalt-nitrogen co-doped carbon nanotubes, whose surfaces are modified with cobalt atoms and nitrogen atoms to form cobalt-nitrogen-carbon bonds. Cobalt atoms use nitrogen atoms as nucleation sites to form a large number of uniformly distributed cobalt atom clusters on the carbon nanotubes; platinum nanoparticles grow on the surface of the carbon nanotubes using the uniformly distributed cobalt atom clusters as nucleation sites.
2. A high-density platinum-supported platinum-carbon catalyst as claimed in claim 1, characterized in that: The platinum nanoparticles have a particle size range of 1.5-4.5 nm, an average particle size of 2.9±2 nm, and are attached to the cobalt-nitrogen doped sites on the surface of the carbon nanotubes.
3. A high-density platinum-supported platinum-carbon catalyst as claimed in claim 1, characterized in that: The diameter of the carbon nanotubes is selected from 1 to 100 nm.
4. A method for preparing a high-density platinum-supported platinum-carbon catalyst as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1, dispersing oxidized carbon nanotubes in deionized water, adding a cobalt-containing precursor and a nitrogen source to obtain a mixed dispersion; S2, freeze-drying the mixed dispersion obtained in step S1 and then calcining it to obtain a cobalt-nitrogen co-doped carbon nanotube material; S3, the cobalt-nitrogen co-doped carbon nanotube material prepared in step S2 is dispersed in a solvent, a platinum salt solution is added, the mixture is heated to reflux, filtered and dried, and a high-density platinum-loaded platinum-carbon catalyst is prepared.
5. The preparation method according to claim 4, characterized in that: The preparation method of the oxidized carbon nanotubes comprises the following steps: using a strong oxidant and a strong acid to modify the surface of the carbon nanotubes, and washing to obtain the oxidized carbon nanotubes.
6. The preparation method according to claim 4, characterized in that: The strong oxidant includes one or more of potassium dichromate, potassium permanganate, and hydrogen peroxide; the strong acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; in step S1, the cobalt-containing precursor is selected from one or more of cobalt metal acetate, cobalt metal nitrate, and cobalt metal chloride.
7. The preparation method according to claim 4, characterized in that: In step S1, the nitrogen source is selected from one or more of dimethylimidazole, urea, and dicyandiamide nitrogen-containing polymers.
8. The preparation method according to claim 4, characterized in that: In step S3, the calcination temperature is 600-1000° C. and the calcination time is 1-4 hours.
9. The preparation method according to claim 4, characterized in that: In step S3, the solvent is selected from oleylamine, ethylene glycol, and a mixed solution of ethylene glycol and water; the reflux temperature is selected from 100-180° C.; and the reflux time is selected from 1-5 hours.
10. Use of the high-density platinum-supported platinum-carbon catalyst according to any one of claims 1 to 3 in a proton exchange membrane fuel cell.
